2019
DOI: 10.1097/md.0000000000016218
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity programs for balance and fall prevention in elderly

Abstract: Background: Due to demographic changes the world's population is progressively ageing. The physiological decay of the elderly adult may lead to a reduction in the ability to balance and an increased risk of falls becoming an important issue among the elderly. In order to counteract the decay in the ability to balance, physical activity has been proven to be effective. The aim of this study is to systematically review the scientific literature in order to identify physical activity programs able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
130
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(193 citation statements)
references
References 54 publications
6
130
0
19
Order By: Relevance
“…Regular exercise is important for maintaining general health status [34]. Physical activity is meant to be a factor that accelerates the increase of bodily functions [9] with a positive impact on balance control [30]. Apart from improving neuroplasticity, physical activity can also modulate multiple systems that are known to regulate neuroinflammation and glial activation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular exercise is important for maintaining general health status [34]. Physical activity is meant to be a factor that accelerates the increase of bodily functions [9] with a positive impact on balance control [30]. Apart from improving neuroplasticity, physical activity can also modulate multiple systems that are known to regulate neuroinflammation and glial activation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Balance impairment and postural instability are also the common incapacitating symptoms of PD, which usually occur in the middle-later stages of the disease [28]. Results from systematic reviews indicate that balance training may have a positive effect on treating postural instability among people with PD and healthy older adults [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…We selected a set of risk factors a priori that had previously been shown to be associated with balance or other measures of physical capability at a single time point in NSHD and other studies (Kuh et al, 2006(Kuh et al, , 2009aBirnie et al, 2011b;Cooper et al, 2011aCooper et al, ,c, 2015Strand et al, 2011a,b;Welmer et al, 2012;D'Andréa Greve et al, 2013;Amemiya et al, 2019;Thomas et al, 2019).…”
Section: Assessment Of Risk Factorsmentioning
confidence: 99%
“…10Most studies have concluded that physical activity, even recreational, is effective to maintain balance control and prevent falls. [11][12][13][14] Several authors have analysed the impact of different kinds of physical exercises and have found that Pilates, stair climbing, vibration Summary Background: Given the public health problem generated by posture and gait disorders, a preventive approach is essential.…”
mentioning
confidence: 99%
“…training, Tai Chi or dancing can significantly improve balance and reduce the risk of falling. 11,[15][16][17][18][19][20][21][22] Given the public health problem created by posture and gait disturbances and falls, a preventive approach seems essential. Of course, this type of program tends to be more effective when it is introduced earlier.…”
mentioning
confidence: 99%